Outcomes of matched sibling donor hematopoietic stem cell transplantation for severe sickle cell disease with myeloablative conditioning and intermediate‐dose of rabbit anti‐thymocyte globulin. Issue 9 (17th April 2014) - Soni, Sandeep; Gross, Thomas G.; Rangarajan, Hemalatha; Baker, K. Scott; Sturm, Mollie; Rhodes, Melissa
Abstract Background Allogeneic hematopoietic stem cell transplantation (HSCT) is a curative therapy for sickle cell disease (SCD) in children. Despite excellent outcomes of matched sibling donor (MSD) HSCT, there is still 5–10% chance of rejection and transplant related mortality (TRM) with 12–23% incidence of graft versus host disease (GVHD). We postulated that an intermediate dose of rabbit anti‐thymocyte globulin (r‐ATG, 10 mg/kg cumulative) would be effective in preventing both rejection and GVHD. Patients and Methods Fifteen patients, median age 5 (range 1.5–18) years, underwent MSD HSCT using busulfan (≥12.8 mg/kg with first dose pharmacokinetics), cyclophosphamide (total 200 mg/kg) and r‐ATG. Bone marrow was the stem cell source; tacrolimus and methotrexate were given for GVHD prophylaxis. Results All patients achieved donor engraftment and there was no TRM. One patient rejected donor cells at 2 months post‐transplant. Majority of the patients had high and sustained level of donor chimerism. None of the patients developed ≥Grade II GVHD. Incidence of CMV (10%) and EBV (9%) reactivations was low with rapid immune‐reconstitution. Overall survival was 100% with event free survival of 93%. Conclusions Eliminating the risks of TRM and GVHD by optimizing the regimen may lead to further acceptance of HSCT for SCD. Pediatr Blood Cancer 2014;61:1685–1689. © 2014 Wiley Periodicals, Inc.